The Influence of Digital Leadership on Employee Engagement through Digital Employee Experience - Ferra Eka Ramadhani (Journal of Creative Power and Ambition (JCPA), 2026)
The following study aims to analyze the influence of Digital Leadership on Employee Engagement through Digital Employee Experience, which serves as a mediating variable. This study employed a quantitative approach through an explanatory research design with 220 employees in organizations that have implemented digital transformation. Data were collected through a questionnaire using a five-point Likert scale and processed using SPSS and the Sobel Test. The results show that Digital Leadership has a significant positive effect on both Digital Employee Experience and Employee Engagement. Furthermore, Digital Employee Experience also has a positive effect on Employee Engagement and is proven to mediate the relationship between Digital Leadership and Employee Engagement. These findings demonstrate that increasing employee engagement in the era of digital transformation requires digital leadership supported by positive digital work experiences. Therefore, organizations need to develop digital leadership competencies and improve the quality of digital work experiences as a strategy to strengthen Employee Engagement and support the success of digital transformation.